Der Fall Grundig(s). Europäische Krisenreaktionsstrategien auf die „Japanische Herausforderung“ im Strukturwandel - Staffel, Florian (Das Ende des „Goldenen Zeitalters“? Der Strukturwandel der 1970er Jahre, seine Rezeption und Folgen aus interdisziplinärer Perspektive)

Der Fisch neben mir – der Einfluss von Individualisierung im Unterricht, sozialer und individueller Vergleiche auf das Fähigkeitsselbstkonzept von Fünftklässler*innen in inklusiven Schulen - Gorges, Julia; Kurz, Katharina; Neumann, Phillip; Hesse, Franziska; Lütje-Klose, Birgit; Wild, Elke (Zeitschrift für Erziehungswissenschaft)
In inklusiven Schulen wird zunehmend ein stärker individualisierter Unterricht verfolgt. Dieser sollte dem negativen Effekt der mittleren Leistung der Bezugsgruppe (z. B. Klasse, Schule) auf das Fähigkeitsselbstkonzept (FSK) von Schülerinnen aufgrund sozialer Vergleiche (Big-Fish-Little-Pond-Effekt [BFLPE]) entgegenwirken. Auch Vergleiche mit individuell gewählten Vergleichstargets könnten sich positiv auf das FSK auswirken. Auf Basis von N = 752 Fünftklässlerinnen aus 28 inklusiven Schulen (Alter: M(SD) = 10.28(0.53), 48 % weiblich) wurde der Effekt der mittleren Gruppenleistung (BFLPE), der Individualisierung im Unterricht und der Vergleich mit individuell ausgewählten Vergleichspartnerinnen – operationalisiert über die Leistungsdifferenz – auf das mathematische FSK geprüft. Die Ergebnisse von Mehrebenen-Regressionsanalysen zeigen einen BFLPE sowie einen signifikant positiven Effekt der Individualisierung im Unterricht. Der Effekt der Leistungsdifferenz zum individuellen Vergleichstarget wurde nicht signifikant. Die Ergebnisse werden bezüglich weiterführender Forschung und praktischer Implikationen zur Förderung eines positiven FSK von Schülerinnen diskutiert. Inclusive schools are increasingly pursuing more individualised instruction, which may counteract the negative effect of the mean performance of the reference group (e.g. class, school) on students’ self-concept of ability (SCA) based on social comparisons (Big-FishLittle-Pond-Effect [BFLPE]). In addition, comparisons with individually selected comparison targets could also have a positive effect on the SCA. Drawing in a sample of N = 752 fifth graders from 28 inclusive schools (age: M(SD) = 10.28(0.53), 48 % female), the effect of mean group performance (BFLPE), individualized instruction and comparisons with individually selected comparison targets - operationalized via the performance difference - on students’ mathematical SCA was examined. The results of multi-level regression analyses show a BFLPE and a significant positive effect of individualised instruction on students’ SCA. The effect of the performance difference to the individual comparison target was not significant. The results are discussed with respect to further research and practical implications for the promotion of a positive SCA in students
Keywords: BiFoKi; Inklusion; Fähigkeitsselbstkonzept; Selbstkonzept; Leistung; Leistungsentwicklung; Mehrebenenanalyse; BFLPE; Big-Fish-Little-Pond; Sonderpädagogischer Förderbedarf; Integration; Sekundarstufe; Bezugsnorm

Der historische Muhammad in der islamischen Theologie. Zur Kriterienfrage in der Leben-Muhammad-Forschung - Ghaffar, Zishan

Der Kopftuchstreit zum wiederholten Mal oder: Das neue einheitliche "Bekenntnisreichen-Recht" - Krimphove, Dieter (ArbR - Arbeitsrecht Aktuell)

Der Liebe will ich singen. Hermann Reutters Begegnung mit dem Mittelalter - Ried, Dennis (Ritter, Tod und Teufel. Hermann Reutter und das Lied)

Der PGR ohne amtliches Mitglied als Impuls für ein neues Rollengefüge - Hofmeister, Lisa; Reis, Oliver (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Der Prosumer im Zentrum des digitalen Energiesystems - Ikonnikova, Svetlana; Schlüter, Alexander; Brandner, Bernadette (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Der steinige Weg vom Wissen zum Können: Zum schwierigen Verhältnis von Theorie und Praxis bei der Betreuung zukünftiger Geschichtslehrkräfte in Langzeitpraktika - Hartung, Olaf; Krebs, Alexandra; Fastlabend-Vargas, Daniel; Meyer-Hamme, Johannes (Theorie und Praxis in der Lehrerbildung.Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)

Der Weg zur Gewalt – Ein zwischenzuständliches Gespräch über Dumpfbacken, Depressionen und Druckwellen. - Jacke, Christoph (Kaput - Magazin für Insolvenz & Pop)

Der Wunsch zu verschwinden - Schulze, Max
Das Buch stellt die drei jüngeren Serien Cool Mild Pure Warm (Streetfile), EPS und Der Wunsch zu verschwinden (Camopedia) des Künstlers Max Schulze vor. Ihm geht es um die Frage, an welchen Orten und auf welche Weise Malerei im Jahr 2021 entsteht: Wie sieht es mit den althergebrachten Kategorisierungen von Farbe und Form, Figuration und Abstraktion oder Fläche und Raum aus? Welche Wege sucht sich vor diesem Hintergrund die heutige Malerei und welche ästhetische Kraft ist ihr eigen? Die 32 Bilder der Serie Der Wunsch zu verschwinden (Camopedia) basieren auf den 32 Farbtönen des Systems «Alpina Feine», die Schulze verwendet, um unterschiedliche Camouflage-Muster zu malen. Dieses speziell kuratierte Farbsystem wird aus Marketinggründen mit Wohlfühlassoziationen verbunden. Diese Aufladung crasht mit der Verwendung des Tarnmusters im militärischen Bereich. Schulze beschäftigt die Frage, warum gerade heute, in einer Zeit, die von vielen politischen und sozialen Veränderungen bestimmt ist, Camouflage in Mode und Design allgegenwärtig ist. Für die Serie Cool Mild Pure Warm (Streetfile) greift Schulze ebenfalls auf Farbsysteme zurück, die er mit Fotos von diversen Farb-Attentaten im öffentlichen Raum kombiniert. So entsteht ein – nicht ganz humorloser – Kommentar zur kommerziellen Nutzung von Farbe in Farbsystemen, aber auch zu deren Zweckentfremdung durch politische «Attacken» im öffentlichen Raum. Der Name der Serie EPS bezieht sich auf ein Material, das unter dem Markennamen Styropor bekannt ist. Schulze klebt es auf abstrakte Malereien, doch nicht vollständig, sondern so, dass Teilbereiche der darunter liegenden Bildebene frei bleiben. Das darunter liegende Bild wird gleichsam verdeckt wie durch die Dämmung geschützt. Es entsteht ein ähnlich ambivalenter Seh-Eindruck wie bei den anderen Serien.
Keywords: Camouflage; Malerei; Wandfarbe; Wohlfühlstrategien; Farbsysteme; Farb-Attentat; öffentlicher Raum; Dämmung; Zwecketfremdung

Derandomization and Local Graph Problems in the Node-Capacitated Clique - Werthmann, Julian

Derivation of socio-technical solution patterns for industry 4.0 problem classes - Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Derivative-Free Multiobjective Trust Region Descent Method Using Radial Basis Function Surrogate Models - Berkemeier, Manuel Bastian; Peitz, Sebastian (Mathematical and Computational Applications)
We present a flexible trust region descend algorithm for unconstrained and convexly constrained multiobjective optimization problems. It is targeted at heterogeneous and expensive problems, i.e., problems that have at least one objective function that is computationally expensive. The method is derivative-free in the sense that neither need derivative information be available for the expensive objectives nor are gradients approximated using repeated function evaluations as is the case in finite-difference methods. Instead, a multiobjective trust region approach is used that works similarly to its well-known scalar pendants. Local surrogate models constructed from evaluation data of the true objective functions are employed to compute possible descent directions. In contrast to existing multiobjective trust region algorithms, these surrogates are not polynomial but carefully constructed radial basis function networks. This has the important advantage that the number of data points scales linearly with the parameter space dimension. The local models qualify as fully linear and the corresponding general scalar framework is adapted for problems with multiple objectives. Convergence to Pareto critical points is proven and numerical examples illustrate our findings.

Des arbitrages éthiques face aux injonctions à la pratique physique dans les programmes de promotion de la santé : le cas des familles populaires en Europe - Grimminger-Seidensticker, Elke; Vieille Marchiset, G.; Knobé, S.; Aceti, M. (SociologieS.)

Design and Analysis of a Regenerative Snubber for a 2.2 kW Active-Clamp Forward Converter with Low-Voltage Output - Korthauer, Bastian; Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))

Design and Experimental Investigation of an Additively Manufactured PMSM Rotor - Urbanek, Stefan; Pauline, Frey; Magerkohl, Sebastian; Zimmer, Detmar; Tasche, Lennart; Schaper, Mirko; Ponick, Bernd
Keywords: Elektromotor; Elektromaschine; Additive Fertigung; AF; AM; Additive Manufacturing; DMRC; KAt

Design and Implementation of a Crowd-based Prototype Validation Platform - N., N.

Design and Implementation of a ReconROS-based Obstacle Avoidance System - Sheikh, Muhammad Aamir
Autonomous mobile robots are becoming increasingly more capable and widespread. Reliable Obstacle avoidance is an integral part of autonomous navigation. This involves real time interpretation and processing of a complex environment. Strict time and energy constraints of a mobile autonomous system make efficient computation extremely desirable. The benefits of employing Hardware/Software co-designed applications are obvious and significant. Hardware accelerators are used for efficient processing of the algorithms by exploiting parallelism. FPGAs are a class of hardware accelerators, which can contain hundreds of small execution units, and can be used for Hardware/Software co-designed application. However, there is a reluctance when it comes to adoption of these devices in well established application domains, such as Robotics, due to a steep learning curve needed for FPGA application design. ReconROS has successfully bridged the gap between robotic and FPGA application development, by providing an intuitive, common development platform for robotic application development for FPGA. It does so by integrating Robotics Operating System(ROS) which is an industry and academia standard for robotics application development, with ReconOS, an operating system for re-configurable hardware. In this thesis an obstacle avoidance system is designed and implemented for an autonomous vehicle using ReconROS. The objectives of the thesis is to demonstrate and explore ReconROS integration within the ROS ecosystem and explore the design process within ReconROS framework, and to demonstrate the effectiveness of Hardware Acceleration in Robotics, by analysing the resulting architectures for Latency and Power Consumption.

Design of a TiAlON multilayer coating: Oxidation stability and deformation behavior - Bobzin, K.; Kalscheuer, C.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Schwiderek, S.; Carlet, M. (Surface and Coatings Technology)

Design of Distributed Reconfigurable Robotics Systems with ReconROS - Lienen, Christian; Platzner, Marco (ACM Transactions on Reconfigurable Technology and Systems)
Robotics applications process large amounts of data in real time and require compute platforms that provide high performance and energy efficiency. FPGAs are well suited for many of these applications, but there is a reluctance in the robotics community to use hardware acceleration due to increased design complexity and a lack of consistent programming models across the software/hardware boundary. In this article, we present ReconROS, a framework that integrates the widely used robot operating system (ROS) with ReconOS, which features multithreaded programming of hardware and software threads for reconfigurable computers. This unique combination gives ROS 2 developers the flexibility to transparently accelerate parts of their robotics applications in hardware. We elaborate on the architecture and the design flow for ReconROS and report on a set of experiments that underline the feasibility and flexibility of our approach.

Design of Distributed Reconfigurable Robotics Systems with ReconROS - Lienen, Christian; Platzner, Marco (arXiv:2107.07208)
Robotics applications process large amounts of data in real-time and require compute platforms that provide high performance and energy-efficiency. FPGAs are well-suited for many of these applications, but there is a reluctance in the robotics community to use hardware acceleration due to increased design complexity and a lack of consistent programming models across the software/hardware boundary. In this paper we present ReconROS, a framework that integrates the widely-used robot operating system (ROS) with ReconOS, which features multithreaded programming of hardware and software threads for reconfigurable computers. This unique combination gives ROS2 developers the flexibility to transparently accelerate parts of their robotics applications in hardware. We elaborate on the architecture and the design flow for ReconROS and report on a set of experiments that underline the feasibility and flexibility of our approach.

Design Principles for a Crowd-Based Prototype Validation Platform - Gottschalk, Sebastian; Aziz, Muhammad Suffyan; Yigitbas, Enes; Engels, Gregor (Software Business - 12th International Conference, ICSOB 2021, Drammen, Norway, December 2-3, 2021, Proceedings)

Design Review of Assembly Workstations using Virtual Prototypes - Gräßler, Iris; Hillebrand, Stefan; Roesmann, Daniel

Design-Based Research in der Hochschullehre am Beispiel der Lehrveranstaltung „Einführung in die Kultur der Mathematik“ - Kempen, Leander; Biehler, Rolf (Lehrinnovationen in der Hochschulmathematik . Konzepte und Studien zur Hochschuldidaktik und Lehrerbildung Mathematik)

Designing a Risk Assessment Tool for Artificial Intelligence Systems - Nagbøl, Per Rådberg; Müller, Oliver; Krancher, Oliver (The Next Wave of Sociotechnical Design)

Designing a Social Media Analytics Dashboard for Government Agency Crisis Communications - Basyurt, Ali Sercan; Marx, Julian; Stieglitz, Stefan; Mirbabaie, Milad (ACIS 2021 Proceedings)
Social media have become a valuable source for extracting data about societal crises and an important outlet to disseminate official information. Government agencies are increasingly turning to social media to use it as a mouthpiece in times of crisis. Gaining intelligence through social media analytics, however, remains a challenge for government agencies, e.g. due to a lack of training and instruments. To mitigate this shortcoming, government agencies need tools that support them in analysing social media data for the public good. This paper presents a design science research approach that guides the development of a social media analytics dashboard for a regional government agency. Preliminary results from a workshop and the resulting design of a first prototype are reported. A user-friendly and responsive design that is secure, flexible, and quick in use could identified as requirements, as well as information display of regional discussion statistics, sentiment, and emerging topics.

Designing of thermosetting plastic components for direct screwing - Auslegung von Duroplastbauteilen zur Direktverschraubung - Moritzer, Elmar; Hillemeyer, Johannes; Kramer, M.; Hopmann, C. (Joining Plastics)

Detection of Defects on Irregular Structured Surfaces by Image Processing Methods for Feature Extraction - Sander, Tom; Lange, Sven; Hilleringmann, Ulrich; Geneis, Volker; Hedayat, Christian; Kuhn, Harald; Gockel, Franz-Barthold (22nd IEEE International Conference on Industrial Technology (ICIT))
During the industrial processing of materials for the manufacture of new products, surface defects can quickly occur. In order to achieve high quality without a long time delay, it makes sense to inspect the work pieces so that defective work pieces can be sorted out right at the beginning of the process. At the same time, the evaluation unit should come close the perception of the human eye regarding detection of defects in surfaces. Such defects often manifest themselves by a deviation of the existing structure. The only restriction should be that only matt surfaces should be considered here. Therefore in this work, different classification and image processing algorithms are applied to surface data to identify possible surface damages. For this purpose, the Gabor filter and the FST (Fused Structure and Texture) features generated with it, as well as the salience metric are used on the image processing side. On the classification side, however, deep neural networks, Convolutional Neural Networks (CNN), and autoencoders are used to make a decision. A distinction is also made between training using class labels and without. It turns out later that the salience metric are best performed by CNN. On the other hand, if there is no labeled training data available, a novelty classification can easily be achieved by using autoencoders as well as the salience metric and some filters.
Keywords: Image Processing; Defect Detection; wooden surfaces; Machine Learning; Neural Networks

Detection of Defects on Irregular Structured Surfaces by Image Processing Methods for Feature Extraction - Sander, Tom; Lange, Sven; Hilleringmann, Ulrich; Geneis, Volker; Hedayat, Christian; Kuhn, Harald; Gockel, Franz-Barthold (2021 22nd IEEE International Conference on Industrial Technology (ICIT))

Determinants for teachers’ intentions to manage heterogeneity in (non-)inclusive primary education. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

Determinants of CDS Trading on Major Banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
This paper empirically investigates determinants of the outstanding net notional amount of credit default swaps (CDSs) contracts written on banks. We extend and complement the previous literature dealing with CDS trading by analyzing a comprehensive set of CDS tradingspecific, bank-fundamental, macroeconomic and bank-institutional determinants. We find that risk hedging clearly dominates an investor’s speculation and arbitrage motive, while the latter, however, exhibits the strongest impact on the outstanding net notional amount of bank CDSs. Furthermore, being classified as a G-SIB, being a constituent of the main CDS index and the equity trading volume may significantly explain changes in the outstanding CDS net notional on banks. The analysis at hand provides important implications for both academics and practitioners, since understanding the trading motives of bank CDS investors provides a deeper insight into the opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Determinants of Loyalty in Online Communities: A Systematic Literature Review - Schlesiger, Laura

Determination of Crystal-Field Splitting Induced by Thermal Oxidation of Titanium - Wojtaszek, Klaudia; Błachucki, Wojciech; Tyrała, Krzysztof; Nowakowski, Michał; Zaja̧c, Marcin; Stȩpień, Joanna; Jagodziński, Paweł; Banaś, Dariusz; Stańczyk, Wiktoria; Czapla-Masztafiak, Joanna; Kwiatek, Wojciech M.; Szlachetko, Jakub; et al. (The Journal of Physical Chemistry A)
Keywords: Physical and Theoretical Chemistry

Determination of Four Priority Polycyclic Aromatic Hydrocarbons in Food Samples by Gas Chromatography – Mass Spectrometry (GC-MS) after Vortex Assisted Dispersive Liquid-Liquid Microextraction (DLLME) - Chormey, Dotse Selali; Tonbul, Güldeniz; Soylu, Güneş; Saygılar, Ahmet; Bakırdere, Sezgin (Analytical Letters)
Keywords: Dispersive liquid-liquid microextraction (DLLME); gas chromatography – mass spectrometry (GC-MS); polycyclic aromatic hydrocarbons; QuEChERS

Determination of local fluid dynamic parameters in structured packings through X-ray tomography: overcoming image resolution restrictions - Bolenz, Lukas; Fischer, Florian; Toye, Dominique; Kenig, Eugeny (Chemical Engineering Science)

Determination of the Interface Structural Resolution of an Industrial X-Ray Computed Tomograph Using a Spherical Specimen and a Gap Specimen Consisting of Gauge Blocks - Busch, M.; Hausotte, T. (Key Engineering Materials)
Industrial X-ray computed tomography (XCT) is a tool for non-destructive testing and a volumetric analysis method with the ability to measure dimensions and geometry inside a component without destroying it. However, XCT is a relatively young technology in the field of dimensional metrology and thus faces several challenges. The achievement of a high measurement resolution, which is re-quired to detect small geometrical features, depends on a variety of influencing factors. In this arti-cle, the interface structural resolution (ISR) as one of the key challenges will be investigated. The two-sphere standard called the hourglass standard allows the determination of the structural resolu-tion by evaluation of the surrounding area of an ideal point contact of two spheres after the CT re-construction in form of a neck-shaped transition. Close to the contact point of the two spheres two opposing surfaces exist. Their distances from each other increase as the distance from the contact point of the two spheres increase. The determination of the distances between the spheres’ surface allows a statement about the ISR. A new developed specimen or standard with a variable gap size consisting of calibrated parallel gauge blocks allows statements about the ISR, too. Because of the higher number of probing points of the gauge block standard the results of the determined ISR are more stable compared to the hourglass standard. This paper compares the results of the computed tomography measurements for the designed interface structural resolution standard with those of the hourglass standard.

Determine similarity of assembly operations using semantic technology - Gräßler, Iris; Roesmann, Daniel; Wiechel, Dominik; Preuß, Daniel; Pottebaum, Jens (54th CIRP Conference on Manufacturing Systems)

Determining the heat flow through the cabinet walls of household refrigerating appliances - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Moczarski, Lukas; Reineke, Michael; Sonnenrein, Gerrit; Hueppe, Christian; Stamminger, Rainer; Hoelscher, Heike; Wagner, Hendrik; Gries, Ulrich; Freiberger, Alfred; et al. (International Journal of Refrigeration)
The increase of the thermal conductivity of PUR foam in the insulation of the cabinet is an important cause for aging processes of household refrigerating appliances. To determine the influence of the PUR foam aging on energy consumption, the development of a new measurement method is necessary be- cause current methods influence the aging behavior of household refrigerators and are therefore not applicable in general. Based on a latent heat sink, constructed as an ice water bucket, a new measure- ment method is developed to determine the k ·A value over time. With this method, the k ·A value of four household refrigerating appliances was determined over an interval of 14 months. The k ·A value increased between 3.6% and 11.5% during this period.

Developing and Evaluating the Concept Data Awareness for K12 Computing Education - Höper, Lukas (21st Koli Calling International Conference on Computing Education Research)
Students often have a lack of understanding and awareness of where, how, and why personal data about them is collected and processed. Especially, when interacting with data-driven digital artifacts, an appropriate perception of the data collection and processing is necessary for self-determination. This dissertation deals with the development and evaluation of a concept called data awareness which aims to foster students’ self-determination interacting with data-driven digital artifacts.
Keywords: data awareness; machine learning; data science education; data-driven digital artifacts; artificial intelligence

Developing first-year students` academic self-efficacy in a distance setting - Büker, Ronja; Jenert, Tobias (19th Biennial EARLI Conference)

Developing first-year students` self-efficacy in a digital dominated semester: An intervention study - Büker, Ronja (JURE 2021 Pre-Conference)

Developing Strategies for Digital Transformation in SMEs with Maturitiy Models - Gausemeier, Jürgen; Pierenkemper, Christoph (Digitalization – Approaches, Case Studies, and Tools for Strategy, Transformation and Implementation)

Developing Strategies for Digital Transformation in SMEs with Maturity Models - Pierenkemper, Christoph; Gausemeier, Jürgen (Digitalization)

Development and Evaluation of a Multi Platform Approach for Augmented Reality Product Configuration - N., N.

Development of a Dynamic Modeling Approach to Simulate a Segmented Distillation Column for Flexible Operation - Bruns, Bastian; Fasel, Henrik; Grünewald, Marcus; Riese, Julia (ChemEngineering)
The need for flexible process equipment has increased over the past decade in the chemical industry. However, process equipment such as distillation columns have limitations that significantly restrict flexible operation. We investigate a segmented tray column designed to allow flexible operation. The design consists of radial trays connected at the downcomer of each tray. Each segment can be operated separately, but depending on the capacity of the feed stream, additional segments can be activated or deactivated. The connection between the trays aims to transfer liquid from one stationary segment to the adjacent inactive segment, thereby reducing the time required for the start-up process. In a case study on the separation of methanol and water, we perform dynamic simulations to assess the reduction in the start-up time of inactive segments. The results confirm the advantages over standard tray designs. The segmented distillation column is a step towards improving the flexibility of separation operations.
Keywords: General Energy; General Engineering; General Chemical Engineering

Development of a Dynamic Strategy to Determine the Optimal Barrel Temperature of Single Screw Extruders - Köllermeier, Jonas; Schöppner, Volker (36th International Conference of the Polymer Processing Society (PPS))

Development of a hybrid crash-relevant car body component with load-adapted thickness properties: Design, manufacturing and testing - Camberg, Alan Adam; Tröster, Thomas; Latuske, Clemens

Development of a Leak Test Method for the Joining technology of Functionally Integrated Lightweight Battery Housings for Electric Vehicles - Schmolke, Tobias; Krüger, Christopher; Merdivan, David; Meschut, Gerson; Urban, Peter

Development of a Method for the Identification of Friction Coefficients in Sheet Metal Materials for the Numerical Simulation of Clinching Processes - Rossel, Moritz Sebastian; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Sheet Metal 2021)
In order to reduce the fuel consumption and consequently the greenhouse emissions, the automotive industry is implementing lightweight constructions in the body in white production. As a result, the use of aluminum alloys is continuously increasing. Due to poor weldability of aluminum in combination with other materials, mechanical joining technologies like clinching are increasingly used. In order to predict relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals affects the geometrical formation of the clinched joint significantly. This paper presents a testing method, which enables to determine the frictional coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum sheets in clinching processes is investigated using numerical simulation. Furthermore, the developed testing method focuses on the specimen geometry as well as the reproduction of the occurring friction conditions between two sheet metal materials in clinching processes. Based on a methodical approach the test setup is explained and the functionality of the method is proven by experimental tests using sheet metal material EN AW6014.
Keywords: Tribology; Sheet Metal; Simulation

Development of a Method for the Identification of Friction Coefficients in Sheet Metal Materials for the Numerical Simulation of Clinching Processes - Rossel, Moritz Sebastian; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
In order to reduce the fuel consumption and consequently the greenhouse emissions, the automotive industry is implementing lightweight constructions in the body in white production. As a result, the use of aluminum alloys is continuously increasing. Due to poor weldability of aluminum in combination with other materials, mechanical joining technologies like clinching are increasingly used. In order to predict relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals affects the geometrical formation of the clinched joint significantly. This paper presents a testing method, which enables to determine the frictional coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum sheets in clinching processes is investigated using numerical simulation. Furthermore, the developed testing method focuses on the specimen geometry as well as the reproduction of the occurring friction conditions between two sheet metal materials in clinching processes. Based on a methodical approach the test setup is explained and the functionality of the method is proven by experimental tests using sheet metal material EN AW6014.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science